1995
DOI: 10.1057/9780230377585
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Capital and Industrialization in Malaysia

Abstract: In the last decades of the twentieth century the small and medium-sized nations of East and South-East Asia have begun a process of potentially enormous political and economic transformation. Explosive growth has occurred already in many parts of the region, and the more slowlygrowing countries are attempting to emulate this vanguard group. The impact of the region upon the world economy has increased rapidly and is likely to continue to do so in the future.In order to understand better economic developments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 0 publications
0
68
0
2
Order By: Relevance
“…As Rasiah (1995: chapter two) has argued, transnational responses are far more complex than that reflected in the above dichotomy. In addition to internal constraints and capabilities, governments and firms often act based on their relative bargaining power, taking cognisance of prevailing alternatives.…”
Section: Environmental Practices Involving Transnationalsmentioning
confidence: 99%
“…As Rasiah (1995: chapter two) has argued, transnational responses are far more complex than that reflected in the above dichotomy. In addition to internal constraints and capabilities, governments and firms often act based on their relative bargaining power, taking cognisance of prevailing alternatives.…”
Section: Environmental Practices Involving Transnationalsmentioning
confidence: 99%
“…An early empirical work addressing this question was that by Lecraw (1973) which found that multinationals tended to rely more on imported inputs for reasons of quality. Other studies on this subject for different countries and sectors are contained in Rasiah (1995) Hobday (1995 and Ernst and O'Connor (1992). This channel of influence is of limited application in the case of software as the different stages of software development are as yet not sufficiently standardised, though there are some signs now, that lower-level coding activities are often subcontracted to smaller software firms.…”
Section: Multinational Firms and Their Influence On Domestic Firmsmentioning
confidence: 99%
“…Rasiah (1995) shows that in Malaysia up to 17.6 per cent of professionals and 10.9 per cent of technicians and supervisors in local firms had prior experience in MNCs. In many cases the entrepreneurs who founded these Malaysian technology firms also had their professional beginnings in foreign hi-tech MNCs.…”
Section: When Mncs Train Do New Skills Spill Over Into the Local Ecomentioning
confidence: 99%
“…In 1975 the government augmented the bite of the NEP with the industrial co-ordination act (ICA), which was created to monitor non-Malay capital vis-à-vis the effort to raise Bumiputra assets. Together the NEP and ICA were often blamed for the decline in FDI between 1975 and1978 (see Rasiah, 1995).…”
mentioning
confidence: 99%